A Comparative Study of Class Action Procedures in France and Lithuania as a Solution to the Legal Vacuum in Indonesia’s Administrative Courts - Jeremiah Jung Liah; Shinta Hadiyantina; Sudarsono Sudarsono (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2026)
Research on the absence of a class action mechanism in Indonesia’s Administrative Courts (PTUN) is crucial given the massive impact of government policies on groups of citizens. This study aims to analyze the legislative rationale behind current regulations, the legal implications of the regulatory vacuum, and to formulate an ideal class action framework for the PTUN through a comparative study with France and Lithuania. The research method employed is normative legal analysis using legislative, conceptual, comparative, and case-based approaches. The findings reveal that the absence of explicit rules leads to legal uncertainty and disparity in judicial decisions, as current procedures rely on civil procedural law that is incompatible with the public law characteristics of the PTUN. Based on the French and Lithuanian models, this study proposes redefining the legal subject as “members of the public” and integrating a standalone class action procedure into the PTUN Law. In conclusion, this transformation is crucial for realizing the principles of speedy and cost-effective adjudication, to ensure collective rights are protected from administrative arbitrariness in accordance with the ideals of the Indonesian welfare state.